The Episcopacy of Nicholas Gallagher, Bishop of Galveston, 1882-1918 - Grace, Madeleine, Sister, C.V.I., 1945- (Summerfield G. Roberts Texas history series., 2020)
"The Episcopacy of Nicholas Gallagher, Bishop of Galveston, 1882-1918 is the first major biography of an important religious figure for the people of Texas. Gallagher became the third Roman Catholic bishop for the diocese in 1882. During his thirty-six year tenure as bishop, he is remembered for his significant contributions to the development of Catholicism in Texas during challenging and very difficult times. Gallagher's episcopacy was marked by the rapid growth of parishes, Catholic schools, and hospitals. He remembered for his missionary efforts among African American Catholics and was particularly instrumental in the rebuilding of churches destroyed by the devastating 1900 hurricane. Grace's work is not only a significant contribution not only to the local history of Galveston but also adds a new understanding to the importance of institutional leadership during a time of transition"--